“A GENTE VIVIA DE TRÁS DOS OUTROS”: processo de reorganização social Krenyê - ALMEIDA , Mônica Ribeiro Moraes de (2017)
In this work, I analyze some constituent elements from Krenyê social reorganization process located in Maranhão. Early 21st century, they claimed belonging people considered extinct, the Krenyê of Bacabal. The invasion by colonial forces led to the loss of territory in the middle of the twentieth century. They passed by the process of dispersion and fragmentation that they went through the loss of territory and lived in the lands of other peoples, leading them to “invisibility” and “silencing”. This process occurs by contingent and relational mode, and had been lived different ways between those claiming Krenyê´s ancestry. Then, I want to emphasize the historical and transitory character of identities and the political and strategic Krenye’s issues, posed by the necessity to achieve the recognition of identity and territory.